Perbedaan Informasi Anatomi Sekuen Proton Density Fat Saturation dan Short Tau Inversion Recovery Pada MRI Shoulder Joint Potongan Coronal Dengan Kasus Rotator Cuff Tear - Maria Adriana Rawi; Ni Putu Rita Jeniyanthi; Ni Luh Putu Sari Widari (STIKes Ibnu Sina Ajibarang, 2023)
MRI of the shoulder joint is a radiologic examination to evaluate internal abnormalities of the shoulder joint. The purpose of this study was to determine whether there is a difference in anatomical information using proton density fat saturation sequences and short tau inversion recovery and to determine which anatomical information is better between PD fat saturation sequences and short tau inversion recovery coronal pieces of MRI examination of the shoulder joint with rotator cuff tear cases. This research method is quantitative experiment. The results of the Friedman test obtained a p value of 0.000 (p value <0.05) interpreted as Ho is rejected so that there is a difference in anatomical information on MRI examination of the shoulder joint in cases of rotator cuff tear with coronal proton density fat sat and coronal STIR sequences. Based on the results of the mean rank value of the Friedman test as a whole, it shows that the MRI examination of the shoulder joint in the case of rotator cuff tear coronal pieces of the proton density Fat Sat sequence has a mean rank of 1.65 and the coronal STIR sequence has a mean rank value of 1.35, which means that the coronal proton density fat sat examination sequence is better in displaying the anatomical image of the MRI shoulder joint compared to the coronal STIR sequence in the case of rotator cuff tear. Keywords:,,,.